OPTIMALISASI DESA WISATA BAHARI MENUJU SAFE COMUNITY TOURISM BERLANDASKAAN FALSAFAH TRI HITA KARANA BERBASIS MEDIA DIGITAL - I Dewa Agung Gde Fanji Pradiptha; I Kadek Artawan; I Nyoman Indhi Wiradika; Novia Ayu Lestari; Ni Putu Geg Mas Widya Candrapinasthy (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
Kalibukbuk is a tourist village known for its beaches, which focus on developing marine tourism attractions and dolphin shows and coral reef tourism. In managing marine tourism, there are several priority issues, including 1) Limited competent resources in providing BHD and First Aid in emergency situations and 2) Low competent resources in utilising mobile applications in marine tourism management to achieve Safe Community Tourism. The target of this activity is the POKMASWAS members, consisting of 40 members. Each activity has five stages, starting from socialisation, training and demonstration, mentoring, evaluation, and Focus Group Discussions for follow-up activities. In the evaluation of BHD and First Aid skills, the average pre-test score of participants was recorded at 130. After training, the average post-test score increased significantly to 246.36, and the Wilcoxon test result showed a p-value < 0.001. These results indicate that the training had a significant impact on improving participants' understanding and skills in performing BHD and First Aid. In the application usage evaluation, the average pre-test score of participants was recorded at 64.00. After training, the average post-test score increased significantly to 94.00, and the Wilcoxon test result showed a p-value < 0.001. These results indicate that the training had a significant impact on improving participants' understanding and skills in using the Banyumilir FAR mobile application.